ANALISIS FRAMING PEMBERITAAN MEDIA DARING PERBEDAAN PEMBERITAAN INDOSPORT DAN BOLASPORT.COM TENTANG KEKALAHAN TIMNAS INDONESIA - Muhamad Irfan Marheinis,; Herpindo, (Journal of Innovation Research and Knowledge, 2021)
Football in Indonesia can be said to have many fans and the People of Indonesia always look forward to the national team competing. However, the achievements of the Indonesian national team are not comparable to the support provided. This became interesting especially the media that highlighted the achievements of the Indonesian national team, which is often disappointing. Like Indosport and Bolasport.com reported the defeat of the national team against Vietnam. In the news is interesting to analyze framing about the defeat of the Indonesian national team. In the process, Entman framing analysis methods are used that can be used in news analysis through discourse studies. The result of this study is that each media in presenting the news will have its own peculiarities meaning in the same issue, the aspects highlighted will vary. Second, the framing done by Indosport and Bolasport.com both has different points of view in preaching the cause of the Indonesian national team's defeat to Vietnam. With the framing done by the media, the media has a role in the framework of criticism and education through their journalistic activities, and it is better than the role can be maximized by the media.